1995
DOI: 10.1002/1097-0142(19951115)76:10+<1948::aid-cncr2820761311>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Is there really a difference in survival of women with squamous cell carcinoma, adenocarcinoma, and adenosquamous cell carcinoma of the cervix?

Abstract: Background. The authors' aim was to assess whether there is a difference in biologic behavior and survival in comparing adenocarcinoma (AdCA), squamous cell carcinoma (SCC), and adenosquamous carcinoma (Ad/SC) of the cervix. Methods. Cancer registrars at 703 hospitals submitted anonymous data on 11,157 patients with cervical cancer diagnosed and/or treated in 1984 and 1990 for a Patient Care Evaluation Study of the American College of Surgeons. Among these patients, 9351 (83.8%) had SCC; 1405 (12.6%), AdCA; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
5
6

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(103 citation statements)
references
References 18 publications
8
84
5
6
Order By: Relevance
“…Some investigators reported that AdCa was more frequently associated with these prognostic factors than SCCa (Kasamatsu et al, 2009). However, other studies found no significant association between these factors and histologic type (Shingleton et al, 1995;Look et al, 1996;Nakanishi et al, 2000;Fregnani et al, 2008). In our series, there were no differences in FIGO stage, tumour size, depth of cervical stromal invasion, parametrial involvement, LVSI or lymph node metastasis between patients with the two histologic types.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Some investigators reported that AdCa was more frequently associated with these prognostic factors than SCCa (Kasamatsu et al, 2009). However, other studies found no significant association between these factors and histologic type (Shingleton et al, 1995;Look et al, 1996;Nakanishi et al, 2000;Fregnani et al, 2008). In our series, there were no differences in FIGO stage, tumour size, depth of cervical stromal invasion, parametrial involvement, LVSI or lymph node metastasis between patients with the two histologic types.…”
Section: Discussioncontrasting
confidence: 73%
“…The prognosis of patients with AdCa after RH is unclear, primarily because studies have been performed on small numbers of patients. Some of these studies found that patients with AdCa have poorer prognosis than do those with SCCa (Hopkins and Morley, 1991;Eifel et al, 1995;Look et al, 1996;Samlal et al, 1997;Lai et al, 1999;Kim et al, 2000;Nakanishi et al, 2000), whereas other reports found no differences in prognosis (AntonCulver et al, 1992;Miller et al, 1993;Shingleton et al, 1995;Grisaru et al, 2001;Ayhan et al, 2004;Lee et al, 2006;Fregnani et al, 2008;Kasamatsu et al, 2009). Therefore, the prognosis after RH and the optimal management of AdCa are still a subject of debate.…”
mentioning
confidence: 99%
“…na grupie 11 tys. pacjentek z rakiem szyjki macicy wskazują jednak na brak różnic w rokowaniu dla poszczegól-nych typów histopatologicznych nowotworu [4].…”
Section: Dyskusjaunclassified
“…No entanto, há uma tendência geral entre os autores em considerar essa variante de pior prognóstico, quando comparada ao carcinoma escamoso ou mesmo ao adenocarcinoma (2,3,7,16,18) . Vale destacar ainda a baixa sobrevida de pacientes com carcinomas de pequenas células e indiferenciados, demonstrada por um estudo recente (1) .…”
Section: Fatores Prognósticos Relevantes Do Carcinoma Adenoescamoso Eunclassified